PEMBERDAYAAN UMKM TAS DI DESA KLUDAN DENGAN PENGENALAN TEKNOLOGI E-MARKET - Dia, Latifah Irsya; Pujianto, Wahyu Eko (Universitas Islam Syekh Yusuf Tangerang, 2024)
This journal aims to empower Micro, Small and Medium Enterprises (MSMEs) in Kludan Village by introducing e-market technology. Counseling and training are carried out to introduce e-markets as a tool for marketing products and increasing market access. In this training, marketing strategies through e-market platforms, product photography techniques, and the use of applications and websites to promote products are explained. In addition, coaching and training is carried out in terms of business management and administration. The results of this community service activity are increasing the knowledge, skills and confidence of MSME actors in marketing their products through e-market technology. In addition, the use of e-market technology also increases market access for MSME bags in Kludan Village so that they can increase income and advance the local economy.MSME, e-market, training, marketing.